Isotype profile and clinical relevance of anticardiolipin antibodies in Sjögren's syndrome. - Jedryka-Goral, A (1992)
The purpose of this study was to determine the occurrence and clinical value of anticardiolipin antibodies in patients with Sjögren's syndrome. Thirty one patients with primary Sjögren's syndrome (all women, mean (SD) age 48.3 (11.2) years) and 32 patients with secondary Sjögren's syndrome with rheumatoid arthritis (all women, mean (SD) age 54.9 (11) years) were studied. IgG, IgM, and IgA anticardiolipin antibodies were determined by a standard enzyme linked immunosorbent assay (ELISA) technique. Anticardiolipin antibodies were found in five patients (16%) with primary Sjögren's syndrome and in seven patients (22%) with secondary Sjögren's syndrome. There was no correlation between anticardiolipin antibodies and the clinical features of the antiphospholipid syndrome (thrombotic events, fetal loss, thrombocytopenia) or extraglandular manifestations of Sjögren's syndrome (arthritis, skin lesions, myositis, polyneuropathy, central nervous system disease, pulmonary and renal disease) in either group. Among the various serological features studied, anticardiolipin antibodies correlated with antinuclear antibodies and antibodies to RNP only in patients with primary Sjögren's syndrome. These results indicate that although anticardiolipin antibodies are often found in serum samples from patients with Sjögren's syndrome, their clinical significance remains unclear.